Presence in the online world a contemplative perspective and practice guide for educators - Jeffrey, Leslie Ann 1967-; Palalas, Agnieszka (Aga); Robert, Karen; Wong, Yuk-Lin Renita (Rowman & Littlefield, 2024)
"Presence in the Online World: A Contemplative Perspective and Practice Guide for Educators addresses the challenges and possibilities of cultivating contemplative presence in an online teaching environment. It brings together proponents of contemplative pedagogy and experts in online education"--